Postoperative opioid prescribing practices in US adult trauma patients: A systematic review. Issue 2 (February 2022) - Rowe, Scott; Zagales, Israel; Fanfan, Dino; Gargano, Toria; Meneses, Evander; Awan, Muhammad; Zagales, Ruth; McKenney, Mark; Elkbuli, Adel
Abstract : BACKGROUND: Opioids have been proven effective in pain management, but overprescription can lead to addiction and abuse. Although current guidelines regarding opioid prescription for chronic and acute pain are available, they fail to address the use of opioids for pain management in traumatic injury patients who undergo operations. The primary objective of this study was to examine opioid prescribing practices for US adult trauma patients who require surgical management, based on prior history of opioid use, type of surgical practice, and age. METHODS: PubMed and Cochrane Journals were used to identify relevant articles between October 2010 and December 29, 2020. Our primary outcome was discrepancies of morphine milligram equivalents (MMEs) prescribed to trauma patients. Significance was defined as p < 0.05. RESULTS: Eleven studies on US trauma patients prescribed opioids were evaluated, creating a total of 30, 249 patients stratified by prior opioid use, age, and race. Patterns seen among patients with prior opioid use include higher MMEs prescribed, lower likelihoods of opioid discontinuation, higher mortality rates, and higher complication rates. Orthopedic surgeons prescribed higher values of MMEs than nonorthopedic surgeons. CONCLUSION: Higher incidences of opioid prescriptions are seen with orthopedic trauma surgery and prior opioid use by the patient. We recommend further development of national protocol implementation for acute pain management for the US trauma population. LEVEL OF EVIDENCE: Systematic review, level III. Abstract : Supplemental digital content is available in the text.